Wideband CMOS low noise amplifiers - Bastos, Ivan Iuri Alves (2016)
Modern fully integrated receiver architectures, require inductorless circuits to achieve their potential low area, low cost, and low power. The low noise amplifier (LNA), which is a key block in such receivers, is investigated in this thesis. LNAs can be either narrowband or wideband. Narrowband LNAs use inductors and have very low noise figure, but they occupy a large area and require a technology with RF options to obtain inductors with high Q. Recently, wideband LNAs with noise and distortion cancelling, with passive loads have been proposed, which can have low NF, but have high power consumption. In this thesis the main goal is to obtain a very low area, low power, and low-cost wideband LNA. First, it is investigated a balun LNA with noise and distortion cancelling with active loads to boost the gain and reduce the noise figure (NF). The circuit is based on a conventional balun LNA with noise and distortion cancellation, using the combination of a common-gate (CG) stage and common-source (CS) stage. Simulation and measurements results, with a 130 nm CMOS technology, show that the gain is enhanced by about 3 dB and the NF is reduced by at least 0.5 dB, with a negligible impact on the circuit linearity (IIP3 is about 0 dBm). The total power dissipation is only 4.8 mW, and the active area is less than 50 x 50 m2 . It is also investigated a balun LNA in which the gain is boosted by using a double feedback structure.We propose to replace the load resistors by active loads, which can be used to implement local feedback loops (in the CG and CS stages). This will boost the gain and reduce the noise figure (NF). Simulation results, with the same 130 nm CMOS technology as above, show that the gain is 24 dB and NF is less than 2.7 dB. The total power dissipation is only 5.4 mW (since no extra blocks are required), leading to a figure-of-merit (FoM) of 3.8 mW1, using 1.2 V supply. The two LNA approaches proposed in this thesis are validated by simulation and by measurement results, and are included in a receiver front-end for biomedical applications (ISM and WMTS), as an example; however, they have a wider range of applications.